Evaluation of a novel liquid embolic agent (precipitating hydrophobic injectable liquid (PHIL)) in an animal endovascular embolization model - Vollherbst, Dominik; Otto, Ruth; Deimling, Andreas von; Pfaff, Johannes; Ulfert, Christian; Kauczor, Hans-Ulrich; Bendszus, Martin; Sommer, Christof-Matthias; Möhlenbruch, Markus Alfred (Journal of neuroInterventional surgery, 2018)
Background The choice of the embolic agent and the embolization technique can have a significant impact on the success of endovascular embolization. Objective To evaluate a novel iodinated copolymer-based liquid embolic agent (precipitating hydrophobic injectable liquid (PHIL)) in the porcine rete mirabile (RM), serving as an endovascular embolization model. Onyx, as an established liquid embolic agent, served as comparator. Materials and methods Sixteen embolization procedures were performed using PHIL (n=8) or Onyx (n=8) as liquid embolic agent. Waiting time between injections was set to 30 or 60 s (n=4 per study group). Survival time after intervention was 2 hours or 7 days. Embolization characteristics (eg, procedure times, number of injections and volume of embolic agent) and embolization extent (percentage of embolized RM in post-interventional x-ray) were assessed. Post-interventional CT and histopathological analyses were performed. Results Embolization characteristics and embolization extent were not significantly different for PHIL and Onyx, including subgroups (eg, embolization extent 44% vs 69% (medians); p=0.101). For PHIL, extension of the waiting time from 30 to 60 s led to a significantly higher embolization extent (24% vs 72% (medians); p=0.035). Moderate disintegration and mild inflammation of the embolized blood vessels were present for both embolic agents. Conclusion PHIL is feasible for transarterial embolization in an acute and subacute endovascular embolization model. In this preliminary experimental in vivo study, embolization characteristics, embolization extent, and biocompatibility seem to be similar to those of Onyx.